History taking by physiotherapists with low back pain patients: are illness perceptions addressed properly?. Issue 13 (18th June 2016) - Roussel, Nathalie A.; Neels, Hedwig; Kuppens, Kevin; Leysen, Marijke; Kerckhofs, Eric; Nijs, Jo; Beetsma, Anneke J.; Van Wilgen, C. Paul
Abstract: Purpose : Despite the increasing evidence that illness perceptions should be addressed in patients, there is a lack of studies evaluating whether physiotherapists question illness perceptions. This study, using a mixed-methods design, investigates the integration of illness perceptions during the first consultation of physiotherapists treating patients with low back pain (LBP). Methods : Thirty-four physiotherapists performed usual history taking in a patient with non-specific LBP. The interview was audiotaped and illness perceptions were indexed using an observational instrument, based on the domains of Leventhal's Common Sense Model. Patients were also asked to fill in the Illness Perception Questionnaire-Revised for LBP. Results : Physiotherapists assessed the illness identity, also perceptions regarding the (physical) cause and controllability of LBP were evaluated. Illness perceptions, such as timeline, consequences, coherence and emotional representation, were poorly assessed. Results of the questionnaire reveal that LBP-patients report overuse, workload and bad posture as primary cause. Patients held positive beliefs about the controllability and have high illness coherence. Conclusion : Belgian physiotherapists mainly question bio-medically oriented illness perceptions, e.g. physical symptoms and causes, but do not sufficiently address psychosocially oriented illness perceptions as recommended in LBP guidelines. Implications for Rehabilitation: Belgian physiotherapists mainly question biomedical oriented illness perceptions (illness identity, provoking factors and treatment control) in patients with low back pain (LBP) during the history taking (i.e. the first consultation). From a bio-psycho-social view psychosocially oriented illness perceptions should be incorporated in the daily routine of physiotherapist's to comply with the bio-psycho-social treatment guidelines for LBP. Continuing education is mandatory in order to improve physiotherapists' knowledge regarding the use of all dimensions of illness perceptions in the assessment of patients with LBP.